Grofilia. Omówienie zjawiska na przykładzie wybranych seriali platformy Netflix - Pigulak, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses the communicative and artistic practice grophilia, which is appropriate for the culture of participation. It consists in the transfictional use of the structures and poetics of digital games in the field of various arts. The points of reference for the analysis of grophilia are three popular series distributed on the Netflix streaming platform: Cyberpunk: Edgerunners, Arcane and Love, Death + Robots. The author analyzes these works, focusing on the systemic character of grofil practices, the aesthetics of grofil texts and their transmedia and transdiscursive specificity. She indicates that grophilia, like genres, can be treated as an artistic strategy that precedes realizations, creates new forms of narration and guides how the work is received.